Pharmacological management of gambling disorder: A systematic review and network meta-analysis - Konstantinos Ioannidis; Cinzia Del Giovane; Charidimos Tzagarakis; Jeremy E. Solly; Samuel J. Westwood; Valeria Parlatini; Henrietta Bowden-Jones; Jon E. Grant; Samuele Cortese; Samuel R. Chamberlain (Comprehensive Psychiatry)
Background: Clinical guidelines remain unclear on which medications for gambling disorder are to be preferred in terms of efficacy and tolerability. We aimed to compare pharmacological treatments for gambling disorder in terms of efficacy and tolerability, using network meta-analysis (NMA). Methods: Based on our pre-registered protocol [CRD42022329520], a structured search was conducted across broad range of databases, for double-blind randomized controlled trials (RCTs) of medications for gambling disorder. Data were independently extracted by two researchers. We used standardized mean differences (SMD) using Hedges' g to measure the efficacy outcomes, and for the effect for tolerability we used dropout rate due to medication side effects, expressed as odds ratio (OR). Confidence in the network estimates was assessed using the CINeMA framework. We followed the PRISMA-NMA guidelines for this work. Outcomes were gambling symptom severity and quality of life (for efficacy), and tolerability. Findings: We included 22 RCTs in the systematic review and 16 RCTs (n = 977 participants) in the NMA. Compared with placebo, moderate confidence evidence indicated that nalmefene [Standardized Mean Difference (SMD): −0.86; 95 % confidence interval (CI: −1.32,-0.41)] reduced gambling severity, followed by naltrexone (SMD: -0.42; 95 %CI: (−0.85,0.01)). Naltrexone (SMD: -0.50; 95 %CI: (−0.85,-0.14)) and nalmefene (SMD: -0.36; 95 %CI: (−0.72,-0.01) were also more beneficial than placebo in terms of quality of life. Olanzapine and topiramate were not more efficacious than placebo. Nalmefene [Odds Ratio (OR): 7.55; 95 %CI: (2.24–25.41)] and naltrexone (OR: 7.82; 95 %CI: (1.26–48.70)) had significantly higher dropout due to side effects (lower tolerability) compared with placebo. Interpretation: Based on NMA, nalmefene and naltrexone currently have the most supportive evidence for the pharmacological treatment of gambling disorder. Further clinical trials of novel compounds, and analysis of individual participant data are needed, to strengthen the evidence base, and help tailor treatments at the individual patient level.